2016
DOI: 10.4236/oje.2016.610058
|View full text |Cite
|
Sign up to set email alerts
|

Was the 4.2 ka Event an Anthropogenic Disaster?

Abstract: The article describes a possible impact of demographic explosion during the Neolith on local ecosystems and on the global climate as well as the role of this explosion in aggravating the course of 4.2 ka cooling event. A possible role of human activity in changing the pattern of mid-latitudes westerlies, monsoons and Walker circulation throughout the Holocene is analyzed. It is explained why during the Holocene Climatic Optimum (HCO) monsoons could have been weaker than today, not stronger, as it is commonly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The abundance of horse bones and images of horses in Maikop culture settlements and burials of c. 3300 BCE in the northern Caucasus led to the suggestion that horseback riding began in the Maikop period ( 75 ). In addition, recent studies of ancient human genomes showed continuous gene flow between Copper Age steppes and Caucasus peoples ( 3 , 4 , 76 , 77 ), and later, during the Bronze Age, between Mesopotamia, Anatolia, the southern and northern Caucasus, and the steppes ( 78 ). This exchange between human groups appears to intensify during a century-long period of cooling and desertification, known as the 4.2-ka (thousand year) event [e.g., ( 79 ) but see ( 80 )], which may have affected subsistence strategies and social networks in the steppe zone [e.g., ( 78 , 81 )].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of horse bones and images of horses in Maikop culture settlements and burials of c. 3300 BCE in the northern Caucasus led to the suggestion that horseback riding began in the Maikop period ( 75 ). In addition, recent studies of ancient human genomes showed continuous gene flow between Copper Age steppes and Caucasus peoples ( 3 , 4 , 76 , 77 ), and later, during the Bronze Age, between Mesopotamia, Anatolia, the southern and northern Caucasus, and the steppes ( 78 ). This exchange between human groups appears to intensify during a century-long period of cooling and desertification, known as the 4.2-ka (thousand year) event [e.g., ( 79 ) but see ( 80 )], which may have affected subsistence strategies and social networks in the steppe zone [e.g., ( 78 , 81 )].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies of ancient human genomes showed continuous gene flow between Copper Age steppes and Caucasus peoples ( 3 , 4 , 76 , 77 ), and later, during the Bronze Age, between Mesopotamia, Anatolia, the southern and northern Caucasus, and the steppes ( 78 ). This exchange between human groups appears to intensify during a century-long period of cooling and desertification, known as the 4.2-ka (thousand year) event [e.g., ( 79 ) but see ( 80 )], which may have affected subsistence strategies and social networks in the steppe zone [e.g., ( 78 , 81 )]. On present evidence, this climatic event seems to be broadly contemporaneous with the arrival of nonlocal horse mitochondrial haplogroups and coat colors in the Caucasus and Anatolia and linked to the expansion of horse husbandry and possibly Indo-European languages [e.g., ( 14 , 75 ) but see ( 82 )].…”
Section: Discussionmentioning
confidence: 99%